Measurable residual disease monitoring provides insufficient lead-time to prevent morphological relapse in the majority of patients with core-binding factor acute myeloid leukemia - Puckrin, Robert (Haematologica, 2020)
Core-binding factor acute myeloid leukemia is characterized by t(8;21) or inv(16) and the fusion proteins RUNX1-RUNX1T1 and CBFB-MYH11. International guidelines recommend monitoring for measurable residual disease every 3 months for 2 years after treatment. However, it is not known whether serial molecular monitoring can predict and prevent morphological relapse. We conducted a retrospective singlecenter study of 114 patients in complete remission who underwent molecular monitoring with real-time quantitative polymerase chain reaction analysis of RUNX1-RUNX1T1 or CBFB-MYH11 transcripts every 3 months. Morphological relapse was defined as re-emergence of >5% blasts and molecular relapse as ≥1 log increase in transcript level between two samples. Over a median follow-up time of 3.7 years (range, 0.2-14.3), remission persisted in 71 (62.3%) patients but 43 (37.7%) developed molecular or morphological relapse. Patients who achieved <3 log reduction in RUNX1- RUNX1T1 or CBFB-MYH11 transcripts at the end of chemotherapy had a significantly higher risk of relapse compared to patients who achieved ≥3 log reduction (61.1% vs. 33.7%, P=0.004). The majority of relapses (74.4%, n=32) were not predicted by molecular monitoring and occurred rapidly with <100 days from molecular to morphological relapse. Molecular monitoring enabled the detection of impending relapse and permitted pre-emptive intervention prior to morphological relapse in only 11 (25.6%) patients. The current practice of molecular monitoring every 3 months provided insufficient lead-time to identify molecular relapses and prevent morphological relapse in the majority of patients with core-binding factor acute myeloid leukemia treated at our institution. Further research is necessary to determine the optimal monitoring strategies for these patients.